CML-DEVS: a specification language for DEVS conceptual models - Hollmann, Diego Ariel (2015)
DEVS models are widely used in the research community, in the industry and even in military or defense departments. Therefore, several software tools exist for modeling and simulating these models. However, each of these tools has its specific input language and a DEVS model described within a particular framework cannot be simulated by a different one. Moreover, the practitioners willing to use one of these tools must have non-trivial programming skills or must ask to a programmer to translate their models into the language of the desired tool. In this paper, we present CML-DEVS, a language that allows the conceptual, abstract or mathematical representation of DEVS models, in terms of mathematical and logical expressions without involving programming issues. Models described with CML-DEVS can be automatically translated (i.e. compiled) into the input language of different modeling and simulation tools. We also present a set of rules to translate CML-DEVS models into models that can be simulated with well-known DEVS frameworks such as DEVS-Suite and PowerDEVS. These rules allow the implementation of a multi-target compiler.